(untitled) (Applied Biological Research, 2016)
Mulberry plant yields deciduous leaves which are the sole food for silkworm Bombyx mori. Among the several diseases affecting mulberry, twig blight caused by Fusarium pallidoroseum (Cooke) Sacc. is prevalent in all mulberry growing areas and attacks all types of mulberry plants (Gunasekhar and Govindaiah, 1994). The disease causes blight of twigs, leaves, saplings and seedlings, besides causing die-back, basal rot and cutting rot, and severely damages plants and affects the quality and quantity of folia (Govindaiah et al., 1990). The affected twigs show dark brown lesions and the leaves above infected portions either turn yellow or dry up leading to severe defoliation. A number of fungicides have been used to control the disease but some of these adversely affect silkworm health and cocoon quality (Gangawar et al., 2000). Some plant extracts possess anti-microbial properties and among these pepper and onion reportedly exhibit broad spectrumactivity against variousfungal phyto pathogens (Greyer and Harborne, 1994). Arya et al. (1995) reported inhibitory effect of the extracts of garlic bulbs and bignonia leaves on mycelial growth of F. pallidoroseum. Gupta et al. (1996) found leaf extracts of Pongamia pinnata highly fungitoxic to F. pallidoroseum. Seed treatment with clove extract of A. sativum was found effective against F. oxysporium f. sp. udum by Kumar et al. (2002). In present study, the efficacy of various plant extracts, observed effective under in vitro conditions